2004
DOI: 10.1007/s00122-004-1650-8
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of chitinase transgenic silver birches (Betula pendula): resistance to fungal diseases

Abstract: A field trial of 15 transgenic birch lines expressing a sugar beet chitinase IV gene and the corresponding controls was established in southern Finland to study the effects of the level of sugar beet chitinase IV expression on birch resistance to fungal diseases. The symptoms caused by natural infections of two fungal pathogens, Pyrenopeziza betulicola (leaf spot disease) and Melampsoridium betulinum (birch rust), were analysed in the field during a period of 3 years. The lines that had shown a high level of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 46 publications
1
52
0
1
Order By: Relevance
“…The sugar beet enzyme also protected tobacco against C. nicotianae and birch against natural infection by Melampsoridium betulinum (birch rust) but not Pyrenopeziza betulicola (leaf spot) (103). These results indicate that effectiveness is dependent on transgene source, plant species, and pathogen sensitivity.…”
Section: Activities and Biological Significance Of Other Inducible Dementioning
confidence: 79%
“…The sugar beet enzyme also protected tobacco against C. nicotianae and birch against natural infection by Melampsoridium betulinum (birch rust) but not Pyrenopeziza betulicola (leaf spot) (103). These results indicate that effectiveness is dependent on transgene source, plant species, and pathogen sensitivity.…”
Section: Activities and Biological Significance Of Other Inducible Dementioning
confidence: 79%
“…Vierheilig et al (72) showed that a 5-to 16-fold increase in the level of chitinase in transgenic Nicotiana sylvestris enhanced its resistance against Rhizoctonia solani but did not alter its susceptibility to colonization by the endomycorrhizal fungus Glomus mosseae. In Betula pendula overexpressing the sugar beet chitinase, resistance against the leaf spot disease organism Pyrenopeziza betulicola and against Melampsoridium betulinum (birch rust) was improved compared with the control, as shown by greenhouse and field trials, respectively (46,49). However, when the impact of the silver birch transformed lines on the ectomycorrhizal fungus Paxillus involutus was assessed in vitro, all but one transformed line showed similar levels of root mycorrhizal colonization (50).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, greenhouse trial studies are only the first step in assessing whether chitinase transgenic trees are harmless, and the results of such studies would not necessarily reflect what would happen in the field. For example, Pasonen et al (49) observed differences in the responses to leaf spot disease between sugar beet chitinasetransformed silver birch trees grown in the greenhouse and trees grown in the field. Long-term field deployment is required to assess the effect of chitinase-transformed trees on nonphytopathogenic fungi and to assess the impact of exudation of a higher level of chitinase by roots on soil mycorrhizal reserves.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a three year field trial of transgenic birch expressing sugar beet chitinase revealed that although plants showed greater resistance in green house trials, in field conditions the trees were susceptible to fungal diseases such as leaf spot, caused by Pyrenopeziza betulicola (Pasonen et al, 2004). At the same time, a three-year trial of Bt-transgenic Populus nigra showed 44 to 100% mortality of larvae feeding on transgenic tree tissues from field-tested plants in comparison with control plants which showed 37% mortality (Hu et al, 2001;Pasonen et al, 2004). Similarly, lignin modification in trees resulted in contrasting phenotypes as in the case of CAD modification.…”
Section: Issues and Concernsmentioning
confidence: 99%